Kajian Proses Produksi Asphalt Concrete Binder Course Menggunakan Asphalt Mixing Plant (AMP) Pada PT. Alhas Jaya Group di Aceh Utara - Iponsyah Putra; Chairil Anwar; Ridhaul Hidayat (Universitas Iskandar Muda, 2022)
Asphalt Mixing Plant (AMP) is used to produce asphalt mixtures. Type of asphalt used in this research is the Asphalt Concrete Binder Course (AC – BC). This study aims to determine the stages of the asphalt manufacturing process and material needed using the Asphalt Mixing Plant (AMP) in one day of production. The method used in this research is the interview method and the direct observation method to the location of the Asphalt Mixing Plant PT. Alhas Jaya Group. There are three stages to produce the Asphalt Concrete Binder Course (AC – BC). The first stage includes hard asphalt, heating, hot asphalt preparation, and weighing. The second stage begins with stockpiling aggregates, transporting aggregates into cold bin, drying/heating, filtering aggregates, and weighing. The third stage is the preparation of additional materials (if needed) and weighing. Producing asphalt concrete binder course for one day of production consist of 15-20 mm coarse aggregate of 90 tons/day or 70 m3/day, 0-5 mm fine aggregate of 72 tons/day or 49 m3/day, fine sand of 88 .2 tonnes/day or 60 m3/day, rock ash of 90 tonnes or 62 m3/day and asphalt of 19.8 tonnes/day or 19 m3/day.